Impact of Transplantation of Cryopreserved and Preincubated with Thymic Multipotent Stromal Cells of Hemopoietic Stem Cells Lethally Irradiated Mice Survival - Nikolska, Kateryna I. (Problems of Cryobiology and Cryomedicine, 2019)
Survival and average life expectancy of 128 CBA mice, intravenously injected the next day after lethalÂ irradiation with 0.5 Ã— 106 cryopreserved syngeneic bone marrow cells (BMCs) or cryopreserved syngeneic cells ofÂ fetal liver (FLCs) of 14 days of gestation were studied. In some experiments, the cells were incubated in vitro afterÂ thawing for 20 hrs with multipotent stromal cells (MSCs) of thymus. It has been established that the contact interactionÂ with thymic MSCs significantly increases the survival of mice as a result of transplantation of hematopoietic stemÂ cells (HSCs) and progenitors of different degrees of maturity. The use of bone marrow cells preincubated withÂ thymic MSCs enhances the survival of irradiated mice at the late post-irradiation stage (after 14â€“16 weeks that wasÂ 13% of the survived animals with 0% in the control). Application of fetal liver cells preincubated with thymic MSCsÂ increases the murine survival rate at the early stage (after 4 weeks it was 40% with 18% in the control) and in 2.4 timesÂ prolong the average life expectancy of animals. The results can be used to improve the HSC transplants and methods for their application. Â Probl Cryobiol Cryomed 2019; 29(2):115â€“124.